Ensino e aprendizagem dos sólidos geométricos: corpos redondos nos anos iniciais do ensino fundamental - Silva, Iraci Ferreira Lima (Universidade Federal do Tocantins, 2025)
In this work, we present the results of a qualitative research that aimed to describe the potential of an approach to teaching round bodies, that is, cone, sphere and cylinder so that students in the early years of elementary school can understand the characteristics and constituent elements of these and the planning of the aforementioned spatial figures. We observed some difficulties faced by students in the study of spatial geometry and in the understanding of geometric solids. To base our study, we used the competencies and skills of the National Common Curricular Base (BNCC) and other curricular guidance documents, in addition to the concepts of Bozza (2015), which focuses on the use of manipulable materials in mathematics teaching. We therefore proposed a workshop to teach about round bodies at this teaching level. The workshop was developed and analyzed with students in the 3rd year of elementary school in a private school in Arraias, in the state of Tocantins. Analyzing the answers to a questionnaire completed by the class after carrying out the activities in the workshop, we found an improvement in the understanding of ideas related to round bodies, characteristics of geometry. Students demonstrated motivation to deepen their knowledge in spatial geometry, especially with regard to round bodies, through workshops that use manipulative materials. However, these results show the appreciation of the proposed workshop to improve the understanding of the study, involving both teachers and students.